Fukushima nuclear accident: preliminary assessment of the risks to non-human biota - Aliyu, Abubakar Sadiq (Oxford University Press, 2015)
This study assesses the 'radio-ecological' impacts of Fukushima nuclear accident on non-human biota using the ERICA Tool, which adopts an internationally verified methodology. The paper estimates the impacts of the accident on terrestrial and marine biota based on the environmental data reported in literature for Japan, China, South Korea and the USA. Discernible impacts have been detected in the marine biota around Fukushima Daiichi nuclear power plant. This study confirms that the Fukushima accident had caused heavier damage to marine bionts compared with terrestrial flora and fauna, in Japan